Discrete wavelet transform signal analyzer - Cox, Pedro Henrique; de Carvalho, Aparecido Augusto [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2007)
This paper addresses the problem of processing biological data, such as cardiac beats in the audio and ultrasonic range, and on calculating wavelet coefficients in real time, with the processor clock running at a frequency of present application-specified integrated circuits and field programmable gate array. The parallel filter architecture for discrete wavelet transform (DWT) has been improved, calculating the wavelet coefficients in real time with hardware reduced up to 60%. The new architecture, which also processes inverse DWT, is implemented with the Radix-2 or the Booth-Wallace constant multipliers. One integrated circuit signal analyzer in the ultrasonic range, including series memory register banks, is presented. © 2007 IEEE.
Keywords: Asynchronous logic circuits; Digital filters; Digital signal processors; Last in last out memory; Logic design; Sequential machines; Signal analysis and synthesis; Discrete wavelet transforms; Field programmable gate arrays (FPGA); Logic circuits; Booth-Wallace constant multipliers; Series memory register banks; Signal analysis